Pedagogical support for the Test of Gross Motor Development – 3 for children with neurotypical development and with Autism Spectrum Disorder: validity for an animated mobile application. (3rd September 2022) - Copetti, Fernando; Valentini, Nadia C.; Deslandes, Andréa C.; Webster, E. Kipling
ABSTRACT: Background : Motor skill assessment is time-consuming and some difficulties are inherent in the administration of motor tests, especially in children with neurodevelopment disorders. Purpose : This study aimed to develop and investigate the face, content, and criterion validity of a Motor Skills Sequential Pictures (MSSP) for the Test of Gross Motor Development – 3 (TGMD-3) to be animated and used in a mobile application (App). Methods : The MSSP was created representing each of the 13 TGMD-3 skills, performance criteria and accuracy was assessed by 23 experts, 52 undergraduate students, and 66 children (range 3–10 years; n = 48 with neurotypical development, n = 18 with Autism Spectrum Disorder, ASD). We conducted two rounds of MSSP expert evaluations to improve the MSSP accuracy. Content validity was conducted with the experts' results using percentage of agreement, content validity coefficient (CVC), kappa, and Chi 2 tests for the first and final version of the MSSP. University students participated in the face validity evaluation of the MSSP final version using percentage of agreement. Further content validity was conducted with experts and university students' scores using Chi 2 . Children participated in the last phase of the study and were requested to identify and perform the skills, and if unsuccessful, they received verbal support based on the motor performance criteria. Results : For content validity results associated with the experts' agreement, scores were high and increased from the first to the second round (CVC from 87.0% to 96.1%; Kappa coefficient >.60, p > .0001). High agreement was obtained for the face validity of all skills (range 94.1–100%). Further, significant associations were found for experts and university students scores for the MSSP final version ( p ≤ .002), providing further evidence for the MSSP content validity. The results for children with neurotypical development showed that children aged 3–4 had more difficulties in identifying the skills compared to older children. Developmental criterion validity was found for several skills (hop, jump, slide, one-hand strike, two-hand strike; p values from <.0001 to .50); the MSSP was a more robust support as children age. In the ASD group, identifying skills was difficult for all ages, but mainly in locomotor skills. Furthermore, an inverse trend was found for the developmental validity criteria for children with ASD for several skills (sSkip, jump, slide, catch, kick; p values from .016 to .050), younger children relied more on the MSSP support to identify the skills. Conclusion : The MSSP, mainly ball skills, proved to be valid to illustrate the TGMD-3 motor performance criteria and may be useful as a visual pedagogical support for children to facilitate skill understanding. Future directions will be to evaluate whether the MSSP animation, in an app-based program, will improve children's motor skill performance.